Peningkatan Hasil Belajar Tematik Terpadu Tema 8 Subtema 3 dengan Model Discovery Learning di Kelas IV SD Negeri 035 Pintu Padang Jae Kabupaten Mandailing Natal - Pulungan, Suryani (Lembaga Yasin AlSys, 2025)
Low learning outcomes among fourth-grade students in integrated thematic learning at SD Negeri 035 Pintu Padang Jae, Mandailing Natal Regency, indicate the need for more effective and participatory learning strategies. This study aims to describe improvements in student learning outcomes through the implementation of the Discovery Learning model on Theme 8 Subtheme 3. The research employed a Classroom Action Research (CAR) design with qualitative and quantitative approaches, conducted over two cycles comprising planning, implementation, observation, and reflection stages. The subjects included the teacher and 22 fourth-grade students. Data were collected through observations, tests, and non-test instruments, including observation sheets, test questions, and attitude journals. The results showed significant improvements in lesson planning from 86.10% to 97.22%, teacher activity from 82.81% to 93.75%, student activity from 81.25% to 90.62%, and learning outcomes with average scores increasing from 78.50 (adequate) to 89.82 (good). The findings conclude that the Discovery Learning model is effective in enhancing the quality of the learning process and student outcomes. The implication is that this model can serve as an alternative learning strategy to foster active involvement and independent understanding in integrated thematic learning.